Metáforas em discursos sobre a imigração e o refúgio na mídia on-line brasileira: um estudo baseado em corpora - Cássio Biz Morosini Filho (2023)
This dissertation attempts to comprehend how metaphors are deployed by media websites in Brazil to represent immigration and refuge. Several studies on this theme have been conducted from traditional media, more specifically Folha de São Paulo (FERREIRA; FLISTER; MOROSINI, 2017; FERREIRA; FLISTER, 2019; MOROSINI, 2020). In this research, we compared data from Folha de São Paulo with independent news websites linked to specific political-ideological tendencies. This choice was made so that we could analyze how different ideological orientations can motivate the use of different metaphors. The theoretical framework that underlies this study is based on assumptions from Cognitive Linguistics more specifically the notion of metaphor scenarios (MUSOLFF, 2006, 2016a; SEMINO; DEMJÉN; DEMMEN, 2016; WODAK, 2020) and extreme metaphors (HART, 2021). In addition to these concepts, we have used texts that study the relationship between metaphor and ideology (GOATLY, 2007), and metaphor use in political discourses (MUSOLFF, 2016a; CHARTERIS-BLACK, 2004). Thus, the general objective of this dissertation is to describe which are the metaphor scenarios and extreme metaphors used in traditional and independent right-wing and left-wing media in order to compare them. To this end, three corpora were compiled: one based on the online website of the newspaper Folha de São Paulo, one on the right-wing website Conexão Política, and one on the left-wing website Esquerda Diário, from 2018 to 2022. Corpora compilation and analysis were performed with the assistance of Sketch Engine (KILGARRIFF et al., 2014). In order to carry out a corpus-based study, the methodology was based on the considerations of Stefanowitsch (2006), who defines a procedure for the study of metaphor in large corpora from the concordance lines found in a corpus. Metaphor identification was carried out through the Metaphor Identification Procedure – Vrije Universitet (STEEN et al., 2010). After the identification, metaphors were grouped according to their source-domain and then analyzed in order to define the metaphor scenarios they build. Among the most frequent source-domains, NATURAL PHENOMENON, MOVEMENT and FORCE were used to build the movement scenario in all corpora. Metaphors from the source-domain VIOLENCE were also employed frequently in the construction of different scenarios, such as physical attack, battle, invasion and war. The way these scenarios were elaborated, along with the extreme metaphors employed, also allowed us to analyze the evaluative aspect in each metaphor scenario. Even though data from Folha de São Paulo presents immigration and refuge in a predominantly negative way, few extreme metaphors were found, indicating a more neutral stance on immigration. In independent media, it was possible to notice the use of scenarios that represent immigration and refuge in a more negative way by the right-wing website, and in a more positive way by the left-wing website.